Mapping Hoaxes, Disinformation, and Hate Speeches in Indonesia - Putri Aisyiyah Rachma Dewi; Awang Dharmawan; Gilang Gusti Aji; Muhammad Danu Winata; Jauhar Wahyuni (Technium Social Sciences Journal, 2023)
Hoaxes and disinformation remain significant challenges for Indonesians in this era of information proliferation. A staggering number of approximately 2,093 hoaxes circulate within the society each year, averaging around 175 hoaxes per month. Recognizing the urgency, the government has taken a proactive stance in the battle against disinformation, hoaxes, and hate speeches within society. Operating under the East Java Department of Communication and Information, they have established an information verification platform accessible at https://klinikhoaks.jatimprov.go.id/. This platform empowers individuals to actively ask for verification of the information they encounter through social media or other online sources. On a monthly basis, the team engages in the verification of a minimum of fifty pieces of information. These items originate from public requests and the team’s independent searches across various publicly accessible information channels. The information being examined covers a wide range of aspects, including the specific problem at hand, information based on region, the categorical classification of the data, and the sources of dissemination media. Due to its inherent diversity, this study aims to comprehensively represent the verified information submissions on the website https://klinikhoaks.jatimprov.go.id/. It employs Krippendorff’s content analysis framework; the research endeavours to cartographically delineate information categories, issue typologies, and media origins. The research population comprises a total of 331 information, simultaneously serving as the research sample. These data points encapsulate the entire information meticulously authenticated by East Java Department of Communication and Information, spanning the temporal interval from February to August 2023. Derived from the findings of this study, it becomes evident that the prevailing information disseminated within the society pertains predominantly to public figures, political matters, government affairs, and fraudulent activities. Concurrently, regarding information dissemination media, TikTok has emerged as a nascent source. However, platforms such as YouTube, WhatsApp, and Facebook are conduits for the most contentious information dissemination.